Managing Nutrition After Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy (CRS-HIPEC): A Qualitative Study of Colorectal Cancer Survivors’ and Caregivers’ Experiences - Kea Turner; Amir Alishahi Tabriz; Ryan Chi-Hsuan Su; Brent J. Small; Emma Hume; Olivia Sprow; Christina Santiago; Jennifer B. Permuth; Benjamin D. Powers; Jeremiah L. Deneve; Sean P. Dineen (Journal of the Academy of Nutrition and Dietetics, 2026)

Corrigendum to “Survival and toxin accumulation in Crassostrea virginica larvae following exposure to various Dinophysis species” [Aquaculture, Volume 602, 30 May 2025, 742294] - Nour Ayache; Marta Sanderson; Jessica Small; Amanda B. Chesler-Poole; Sabrina D. Giddings; Lisa Campbell; Vera L. Trainer; Michael L. Brosnahan; Juliette L. Smith (Aquaculture, 2025)

Survival and toxin accumulation in Crassostrea virginica larvae following exposure to various Dinophysis species - Nour Ayache; Marta Sanderson; Jessica Small; Amanda B. Chesler-Poole; Sabrina D. Giddings; Lisa Campbell; Vera L. Trainer; Michael L. Brosnahan; Juliette L. Smith (Aquaculture, 2025)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Application of Sentinel-1 InSAR to monitor tailings dams and predict geotechnical instability: practical considerations based on case study insights - Nahyan M. Rana; Keith B. Delaney; Stephen G. Evans; Evan Deane; Andy Small; Daniel A. M. Adria; Scott McDougall; Negar Ghahramani; W. Andy Take (Bulletin of Engineering Geology and the Environment, 2024)
Tailings storage facilities (TSFs) impound mining waste behind dams to ensure public safety, but failure incidents have prompted calls for more robust monitoring programs. Satellite-based interferometric synthetic aperture radar (InSAR) has grown in popularity due to its ability to remotely detect millimeter-scale displacements in most urban and some natural terrains. However, there remains a limited understanding of whether InSAR can be as accurate or representative as on-the-ground instruments, whether failures can be predicted in advance using InSAR, and what variables govern the quality and reliability of InSAR results. To address these gaps, we analyze open-source, medium-resolution Sentinel-1 data to undertake a ground-truth assessment at a test site and a forensic analysis of five failure cases. We use a commercial software with an automated Persistent Scatterer (PS) workflow (SARScape Analytics) for all case study sites except one and a proprietary algorithm (SqueeSAR) with a dual PS and Distributed Scatterer (DS) algorithm for the ground-truth site and one forensic case. The main goal is to deliver practical insights regarding the influence of algorithm/satellite selection, environmental conditions, site activity, coherence thresholds, satellite-dam geometry, and failure modes. We conclude that Sentinel-1 InSAR can serve as a hazard-screening tool to help guide where to undertake targeted investigations; however, most potential failure modes may not exhibit InSAR-detectable accelerations that could assist with time-of-failure prediction in real time. As such, long-term monitoring programs should ideally be integrated with a combination of remote sensing and field instrumentation to best support engineering practice and judgment.

Application of a Geochemically Informed Leak Detection (GILD) Model to CO2 Injection Sites on the United States Gulf Coast - Jiaan Wang; Wei Xiong; Mitchell J. Small; James B. Gardiner; Brian W. Stewart; R. Burt Thomas; J. Alexandra Hakala; Christina L. Lopano (International Journal of Greenhouse Gas Control, 2024)

A geochemically informed leak detection (GILD) model for CO2 injection sites - Jiaan Wang; Wei Xiong; James B. Gardiner; Brandon C. McAdams; Brian W. Stewart; R. Burt Thomas; J. Alexandra Hakala; Christina L. Lopano; Mitchell J. Small (Applied Geochemistry, 2023)

SARS-CoV-2 vaccinated hamsters show distinctive lung pathology with Th-2 skewed immune response following infection - R. de Jong; S. Vreman; K. Wiese; B. Small; N. Gerhards; K. Bewley; Y. Hall; F.J. Salguero; M. Caroll; N. Oreshkova (Journal of Comparative Pathology, 2023)

Development and Evaluation of High-Density SNP Arrays for the Eastern Oyster Crassostrea virginica - Ximing Guo; Jonathan B. Puritz; Zhenwei Wang; Dina Proestou; Standish Allen; Jessica Small; Klara Verbyla; Honggang Zhao; Jaime Haggard; Noah Chriss; Dan Zeng; Kathryn Lundgren; et al. (Marine Biotechnology, 2023)

Detection of toxins and harmful algal bloom cells in shellfish hatcheries and efforts toward removal - Marta P. Sanderson; Karen L. Hudson; Lauren S. Gregg; Amanda B. Chesler-Poole; Jessica M. Small; Kimberly S. Reece; Ryan B. Carnegie; Juliette L. Smith (Aquaculture, 2023)

Correction to: Evaluation of a multi-model approach to estimate leaf wetness duration: an essential input for disease alert systems - Andre B. Gama; Daniel Perondi; Megan M. Dewdney; Clyde W. Fraisse; Ian M. Small; Natalia A. Peres (Theoretical and Applied Climatology, 2022)

Evaluation of a multi-model approach to estimate leaf wetness duration: an essential input for disease alert systems - Andre B. Gama; Daniel Perondi; Megan M. Dewdney; Clyde W. Fraisse; Ian M. Small; Natalia A. Peres (Theoretical and Applied Climatology, 2022)

On the control of subantarctic stratification by the ocean circulation - R. Justin Small; Alice K. DuVivier; Daniel B. Whitt; Matthew C. Long; Ian Grooms; William G. Large (Climate Dynamics, 2021)

Similar neurocognitive outcomes after 48 weeks in HIV-1-infected participants randomized to continue tenofovir/emtricitabine + atazanavir/ritonavir or simplify to abacavir/lamivudine + atazanavir - Kevin Robertson; Paul Maruff; Lisa L. Ross; David Wohl; Catherine B Small; Howard Edelstein; Mark S. Shaefer (Journal of NeuroVirology, 2019)

Monitoring concentration and isotopic composition of methane in groundwater in the Utica Shale hydraulic fracturing region of Ohio - E. Claire Botner; Amy Townsend-Small; David B. Nash; Xiaomei Xu; Arndt Schimmelmann; Joshua H. Miller (Environmental Monitoring and Assessment, 2018)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Leveraging constraints and biotelemetry data to pinpoint repetitively used spatial features - Brian M. Brost; Mevin B. Hooten; Robert J. Small (Ecology, 2017)
Satellite telemetry devices collect valuable information concerning the sites visited by animals, including the location of central places like dens, nests, rookeries, or haul‐outs. Existing methods for estimating the location of central places from telemetry data require user‐specified thresholds and ignore common nuances like measurement error. We present a fully model‐based approach for locating central places from telemetry data that accounts for multiple sources of uncertainty and uses all of the available locational data. Our general framework consists of an observation model to account for large telemetry measurement error and animal movement, and a highly flexible mixture model specified using a Dirichlet process to identify the location of central places. We also quantify temporal patterns in central place use by incorporating ancillary behavioral data into the model; however, our framework is also suitable when no such behavioral data exist. We apply the model to a simulated data set as proof of concept. We then illustrate our framework by analyzing an Argos satellite telemetry data set on harbor seals ( Phoca vitulina ) in the Gulf of Alaska, a species that exhibits fidelity to terrestrial haul‐out sites.

Addressing key issues in the consanguinity-related risk of autosomal recessive disorders in consanguineous communities: lessons from a qualitative study of British Pakistanis - A. Darr; N. Small; W. I. U. Ahmad; K. Atkin; P. Corry; B. Modell (Journal of Community Genetics, 2016)

Animal movement constraints improve resource selection inference in the presence of telemetry error - Brian M. Brost; Mevin B. Hooten; Ephraim M. Hanks; Robert J. Small (Ecology, 2015)
Multiple factors complicate the analysis of animal telemetry location data. Recent advancements address issues such as temporal autocorrelation and telemetry measurement error, but additional challenges remain. Difficulties introduced by complicated error structures or barriers to animal movement can weaken inference. We propose an approach for obtaining resource selection inference from animal location data that accounts for complicated error structures, movement constraints, and temporally autocorrelated observations. We specify a model for telemetry data observed with error conditional on unobserved true locations that reflects prior knowledge about constraints in the animal movement process. The observed telemetry data are modeled using a flexible distribution that accommodates extreme errors and complicated error structures. Although constraints to movement are often viewed as a nuisance, we use constraints to simultaneously estimate and account for telemetry error. We apply the model to simulated data, showing that it outperforms common ad hoc approaches used when confronted with measurement error and movement constraints. We then apply our framework to an Argos satellite telemetry data set on harbor seals ( Phoca vitulina ) in the Gulf of Alaska, a species that is constrained to move within the marine environment and adjacent coastlines.

Nitrogen transformations at the sediment–water interface across redox gradients in the Laurentian Great Lakes - Gaston E. Small; James B. Cotner; Jacques C. Finlay; Rebecca A. Stark; Robert W. Sterner (Hydrobiologia, 2014)

Examining the family-centred approach to genetic testing and counselling among UK Pakistanis: a community perspective - A. Darr; N. Small; W. I. U. Ahmad; K. Atkin; P. Corry; J. Benson; R. Morton; B. Modell (Journal of Community Genetics, 2013)

The genetics and genomics of Syngnathidae: pipefishes, seahorses and seadragons - K. B. Mobley; C. M. Small; A. G. Jones (Journal of Fish Biology, 2011)
The goal of this review was to provide a historical overview of how molecular techniques have increased the understanding of the ecology and evolution of the family Syngnathidae (pipefishes, seahorses and seadragons). Molecular studies based primarily on mitochondrial DNA markers have proved their worth by elucidating complex phylogenetic relationships within the family. Phylogeographic studies, which have revealed how life‐history traits and past climatic events shape geographic distributions and patterns of genetic variation within syngnathid species, also provide interesting case studies for the conservation and management of threatened species. The application of microsatellite DNA markers has opened a floodgate of studies concerned with the breeding biology of these fishes, which are interesting due to their unique reproductive mode of male pregnancy. Research in this area has contributed significantly to the understanding of mating patterns and sexual selection. Molecular markers may also be employed in studies of demography, migration and local breeding population sizes. Genomic studies have identified genes that are probably involved in male pregnancy and promise additional insights into various aspects of syngnathid biology at the level of the gene. Despite these advances, much more remains to be explored. Goals for future research should include: (1) a more inclusive phylogeny to resolve outstanding issues concerning the relationships within the family and higher order taxa, (2) a broader use of molecular studies to aid management and conservation efforts, (3) the inclusion of more genera in comparative behavioural studies and (4) the continued development of genomic resources for syngnathids to facilitate comparative genomic work.

Population structure of the dusky pipefish ( Syngnathus floridae ) from the Atlantic and Gulf of Mexico, as revealed by mitochondrial DNA and microsatellite analyses - Kenyon B. Mobley; Clayton M. Small; Nathaniel K. Jue; Adam G. Jones (Journal of Biogeography, 2010)
Aim To elucidate the historical phylogeography of the dusky pipefish ( Syngnathus floridae ) in the North American Atlantic and Gulf of Mexico ocean basins. Location Southern Atlantic Ocean and northern Gulf of Mexico within the continental United States. Methods A 394‐bp fragment of the mitochondrial cytochrome b gene and a 235‐bp fragment of the mitochondrial control region were analysed from individuals from 10 locations. Phylogenetic reconstruction, haplotype network, mismatch distributions and analysis of molecular variance were used to infer population structure between ocean basins and time from population expansion within ocean basins. Six microsatellite loci were also analysed to estimate population structure and gene flow among five populations using genetic distance methods ( F ST , Nei’s genetic distance), isolation by distance (Mantel’s test), coalescent‐based estimates of genetic diversity and migration patterns, Bayesian cluster analysis and bottleneck simulations. Results Mitochondrial analyses revealed significant structuring between ocean basins in both cytochrome b ( Φ ST = 0.361, P 0.0001; Φ CT = 0.312, P 0.02) and control region ( Φ ST = 0.166, P 0.0001; Φ CT = 0.128, P 0.03) sequences. However, phylogenetic reconstructions failed to show reciprocal monophyly in populations between ocean basins. Microsatellite analyses revealed significant population substructuring between all locations sampled except for the two locations that were in closest proximity to each other (global F ST value = 0.026). Bayesian analysis of microsatellite data also revealed significant population structuring between ocean basins. Coalescent‐based analyses of microsatellite data revealed low migration rates among all sites. Mismatch distribution analysis of mitochondrial loci supports a sudden population expansion in both ocean basins in the late Pleistocene, with the expansion of Atlantic populations occurring more recently. Main conclusions Present‐day populations of S. floridae do not bear the mitochondrial DNA signature of the strong phylogenetic discontinuity between the Atlantic and Gulf coasts of North America commonly observed in other species. Rather, our results suggest that Atlantic and Gulf of Mexico populations of S. floridae are closely related but nevertheless exhibit local and regional population structure. We conclude that the present‐day phylogeographic pattern is the result of a recent population expansion into the Atlantic in the late Pleistocene, and that life‐history traits and ecology may play a pivotal role in shaping the realized geographical distribution pattern of this species.

Genetic divergence among sympatric colour morphs of the Dalmatian wall lizard (Podarcis melisellensis) - K. Huyghe; M. Small; B. Vanhooydonck; A. Herrel; Z. Tadić; R. Van Damme; T. Backeljau (Genetica, 2010)

Molecular evolution of the Li/li chemical defence polymorphism in white clover ( Trifolium repens L.) - K. M. OLSEN; B. L. SUTHERLAND; L. L. SMALL (Molecular Ecology, 2007)
White clover ( Trifolium repens ) is naturally polymorphic for cyanogenesis (hydrogen cyanide release following tissue damage). The ecological factors favouring cyanogenic and acyanogenic plants have been examined in numerous studies over the last half century, making this one of the best‐documented examples of an adaptive polymorphism in plants. White clover cyanogenesis is controlled by two, independently segregating Mendelian genes: Ac/ac controls the presence/absence of cyanogenic glucosides; and Li/li controls the presence/absence of their hydrolysing enzyme, linamarase. In this study, we examine the molecular evolution and population genetics of Li as it relates to the cyanogenesis polymorphism. We report here that Li exists as a single‐copy gene in plants possessing linamarase activity, and that the absence of enzyme activity in li/li plants is correlated with the absence of much or all of the gene from the white clover genome. Consistent with this finding, we confirm by reverse transcription–polymerase chain reaction that Li gene expression is absent in plants lacking enzyme activity. In a molecular population genetic analysis of Li and three unlinked genes using a worldwide sample of clover plants, we find an absence of nucleotide variation and statistically significant deviations from neutrality at Li ; these findings are consistent with recent positive directional selection at this cyanogenesis locus.

KILLER WHALES AND MARINE MAMMAL TRENDS IN THE NORTH PACIFIC—A RE‐EXAMINATION OF EVIDENCE FOR SEQUENTIAL MEGAFAUNA COLLAPSE AND THE PREY‐SWITCHING HYPOTHESIS - Paul R. Wade; Vladimir N. Burkanov; Marilyn E. Dahlheim; Nancy A. Friday; Lowell W. Fritz; Thomas R. Loughlin; Sally A. Mizroch; Marcia M. Muto; Dale W. Rice; Lance G. Barrett‐Lennard; Nancy A. Black; Alexander M. Burdin; et al. (Marine Mammal Science, 2007)
Springer et al . (2003) contend that sequential declines occurred in North Pacific populations of harbor and fur seals, Steller sea lions, and sea otters. They hypothesize that these were due to increased predation by killer whales, when industrial whaling's removal of large whales as a supposed primary food source precipitated a prey switch. Using a regional approach, we reexamined whale catch data, killer whale predation observations, and the current biomass and trends of potential prey, and found little support for the prey‐switching hypothesis. Large whale biomass in the Bering Sea did not decline as much as suggested by Springer et al ., and much of the reduction occurred 50–100 yr ago, well before the declines of pinnipeds and sea otters began; thus, the need to switch prey starting in the 1970s is doubtful. With the sole exception that the sea otter decline followed the decline of pinnipeds, the reported declines were not in fact sequential. Given this, it is unlikely that a sequential megafaunal collapse from whales to sea otters occurred. The spatial and temporal patterns of pinniped and sea otter population trends are more complex than Springer et al . suggest, and are often inconsistent with their hypothesis. Populations remained stable or increased in many areas, despite extensive historical whaling and high killer whale abundance. Furthermore, observed killer whale predation has largely involved pinnipeds and small cetaceans; there is little evidence that large whales were ever a major prey item in high latitudes. Small cetaceans (ignored by Springer et al .) were likely abundant throughout the period. Overall, we suggest that the Springer et al . hypothesis represents a misleading and simplistic view of events and trophic relationships within this complex marine ecosystem.

Site‐level evaluation of satellite‐based global terrestrial gross primary production and net primary production monitoring - David P. Turner; William D. Ritts; Warren B. Cohen; Thomas K. Maeirsperger; Stith T. Gower; Al A. Kirschbaum; Steve W. Running; Maosheng Zhao; Steven C. Wofsy; Allison L. Dunn; Beverly E. Law; John L. Campbell; et al. (Global Change Biology, 2005)
Operational monitoring of global terrestrial gross primary production (GPP) and net primary production (NPP) is now underway using imagery from the satellite‐borne Moderate Resolution Imaging Spectroradiometer (MODIS) sensor. Evaluation of MODIS GPP and NPP products will require site‐level studies across a range of biomes, with close attention to numerous scaling issues that must be addressed to link ground measurements to the satellite‐based carbon flux estimates. Here, we report results of a study aimed at evaluating MODIS NPP/GPP products at six sites varying widely in climate, land use, and vegetation physiognomy. Comparisons were made for twenty‐five 1 km 2 cells at each site, with 8‐day averages for GPP and an annual value for NPP. The validation data layers were made with a combination of ground measurements, relatively high resolution satellite data (Landsat Enhanced Thematic Mapper Plus at ∼30 m resolution), and process‐based modeling. There was strong seasonality in the MODIS GPP at all sites, and mean NPP ranged from 80 g C m −2 yr −1 at an arctic tundra site to 550 g C m −2 yr −1 at a temperate deciduous forest site. There was not a consistent over‐ or underprediction of NPP across sites relative to the validation estimates. The closest agreements in NPP and GPP were at the temperate deciduous forest, arctic tundra, and boreal forest sites. There was moderate underestimation in the MODIS products at the agricultural field site, and strong overestimation at the desert grassland and at the dry coniferous forest sites. Analyses of specific inputs to the MODIS NPP/GPP algorithm – notably the fraction of photosynthetically active radiation absorbed by the vegetation canopy, the maximum light use efficiency (LUE), and the climate data – revealed the causes of the over‐ and underestimates. Suggestions for algorithm improvement include selectively altering values for maximum LUE (based on observations at eddy covariance flux towers) and parameters regulating autotrophic respiration.

Integrated Environmental Assessment - Anu Ramaswami; Jana B. Milford; Mitchell J. Small (Journal of Industrial Ecology, 2004)

Effect of dietary cortisol administration on growth and reproductive success of channel catfish - B. C. Small (Journal of Fish Biology, 2004)
The effect of cortisol administration on reproductive performance was investigated in channel catfish Ictalurus punctatus broodfish. Cortisol was added to a commercial catfish feed by dissolving in ethanol and spraying the feed to yield a dietary concentration of 150 mg kg −1 feed. The cortisol diet and the control (no cortisol) diet were offered at a rate of 1% of biomass to three replicate ponds each containing 28 female and 14 male broodfish, respectively, three times per week for 11 weeks. Spawning began 10 days after the start of the experiment, and continued for 10 weeks. In fish fed cortisol, body mass and the hepato‐somatic index were reduced ( P ≤ 0·02) and concentrations of plasma cortisol and glucose were significantly higher ( P ≤ 0·0003) compared to those of controls. The relative frequency of spawning was similar between the two treatments; however, cortisol‐fed channel catfish had an average of 47·1% more spawns than the control‐fed fish. On average, there were 25·5 spawns per pond in the treated groups compared to 12·3 spawns per control pond ( P = 0·10). No effect was observed on egg production, with individual egg mass, fecundity, and hatching success being similar ( P ≥ 0·27) for both treatments. Despite the observed negative effects of cortisol on somatic and hepatic growth, the increased reproductive output coupled with no observable effects on the eggs or hatching success demonstrates that cortisol does not suppress channel catfish reproduction.

Pathogen loads, clearance and plasma cortisol response in channel catfish, Ictalurus punctatus (Rafinesque), following challenge with Edwardsiella ictaluri - A L Bilodeau; B C Small; W R Wolters (Journal of Fish Diseases, 2003)

Functional analysis of TamA, a coactivator of nitrogen-regulated gene expression in Aspergillus nidulans - J. A. Small; R. B. Todd; M. C. Zanker; S. Delimitrou; M. J. Hynes; M. A. Davis (Molecular Genetics and Genomics, 2001)

Reduced-Form Modelling of Surface Water and Soil Chemistry for the Tracking and Analysis Framework - R. Sinha; M. J. Small; P. F. Ryan; T. J. Sullivan; B. J. Cosby (Water, Air, & Soil Pollution, 1998)

Mechanical alterations in smooth muscle from mice lacking desmin - R. Sjuve; A. Arner; Z. Li; B. Mies; D. Paulin; M. Schmittner; J. V. Small (Journal of Muscle Research and Cell Motility, 1998)

Biogeochemical gradients in the lower Columbia River - F. G. Prahl; L. F. Small; B. A. Sullivan; J. Cordell; C. A. Simenstad; B. C. Crump; J. A. Baross (Hydrobiologia, 1997)